BSmart: desenvolvimento rigoroso de aplicações Java Card com base no método formal B - Gomes, Bruno Emerson Gurgel (2007)
Java Card technology allows the development and execution of small applications embedded in smart cards. A Java Card application is composed of an external card client and of an application in the card that implements the services available to the client by means of an Application Programming Interface (API). Usually, these applications manipulate and store important information, such as cash and confidential data of their owners. Thus, it is necessary to adopt rigor on developing a smart card application to improve its quality and trustworthiness. The use of formal methods on the development of these applications is a way to reach these quality requirements. The B method is one of the many formal methods for system specification. The development in B starts with the functional specification of the system, continues with the application of some optional refinements to the specification and, from the last level of refinement, it is possible to generate code for some programming language. The B formalism has a good tool support and its application to Java Card is adequate since the specification and development of APIs is one of the major applications of B. The BSmart method proposed here aims to promote the rigorous development of Java Card applications up to the generation of its code, based on the refinement of its formal specification described in the B notation. This development is supported by the BSmart tool, that is composed of some programs that automate each stage of the method; and by a library of B modules and Java Card classes that model primitive types, essential Java Card API classes and reusable data structures